Elaboración de una bebida hidratante a base de lactosuero y enriquecida con vitaminas - Chóez Alcívar, Johanna (2010)
For a couple of decades ago the dairy industry is highly polluting derivative, obtained in the process of making cheese when the liquid fraction is separated from milk curd, called whey, this product has excellent nutritional properties arising from its lactose content, protein, vitamins and minerals. Because this nutrient is important that the dairy industry whey used as food at the same time provide for the human nutritional intake. The following work aims to build on the nutritional properties that offer the whey for the development of a hypotonic sports drink on base. In the first part of the work, describe the product, market segment, characteristics, types, composition, nature, applications, current products, benefits of whey, methods of preparation of whey-based beverage as well as on sports drinks. In the next part will be carried out experimental tests of the preparation of the drink which will be held on experimental design, physico-chemical, microbiological, sensory evaluation, stability of the beverage rack. It will recommend the necessary equipment and will present an analysis of manufacturing costs.